Maternal nutritional knowledge, practice and their associated factors during pregnancy in Addis sub city health centers, Addis Ababa, Ethiopia - Shegaw Tesfa; Zewdie Aderaw; Abebe Tesfaye; Haimanot Abebe; Tadesse Tsehay (Elsevier, 2022)
Introduction: Maternal dietary knowledge and practice is an essential element in ensuring positive pregnancy-related outcomes, optimal gestational weight gain, reduce complications and positive birth outcomes, and the overall health of mothers. 3.5 million mothers dead annually due to undernutrition; which resulted from a deficit in nutritional knowledge and practices in third world countries, especially in Ethiopia, so it needs further investigation. Objective: To assess maternal nutritional knowledge, practice, and their associated factors during pregnancy in Addis Sub-city health centers, Addis Ababa, Ethiopia, 2021. Method and Materials: A cross-sectional study design was conducted in the Addis sub-city from April 1 to May 30, 2021. A total of 363 pregnant mothers attending ANC clinics participated in the study. Eligible pregnant mothers were selected using a systematic random sampling method from three health centers proportionally. Data were collected using an interviewer-administered questionnaire prepared in English and translated into the national language, Amharic. The data were entered into Epi-data version 3.1 and exported to SPSS version 26. Bivariate and multivariate logistics regression analyses were employed to identify factors associated with dietary knowledge and practices. Results: Maternal dietary knowledge was 73.9 % and dietary practices 63.9 % during pregnancy. Being daily laborer (AOR = 0.2, 95 %CI:(0.1-0.9)), husband's educational level (AOR = 4.3, 95 % CI: (1.1-6.3)), family size (AOR = 1.6, 95 % CI: (2.9-4.6)). Monthly income (AOR = 0.2, 95 % CI: (0.0-0.9)), having chronic illness (AOR = 3.3, 95 % CI, (1.3-8.1)), BMI (AOR = 3.6, 95 %CI: (1.2-5.4)), pregnancy interval (AOR = 0.1, 95 %CI: (0.0-0.4)), ANC visit (AOR = 2.2, 95 % CI:(1.6-2.7)), were significantly associated with dietary knowledge. Being employed (AOR = 1.7, 95 % CI:(1.1-3.9)), husband's educational level (AOR = 5.3, 95 % CI: (1.3-7.9)), husband's occupation (AOR = 2.4, 95 %CI: (1.0-5.7)), family size (AOR = 8.7, 95 % CI: (3.2-12.5)) and BMI (AOR = 6.2, 95 % CI: (1.9-14.9) were statistical associated with dietary practice. Conclusion and Recommendation: The overall maternal dietary knowledge was good and dietary practices were poor. Women's occupational status, husband's education, family size, and BMI were associated with both knowledge and practices while monthly income, having chronic illness and pregnancy interval and ANC visit was only associated with knowledge. Therefore enhancing maternal educational status increases their dietary knowledge and practices.